Novel saturated hexacyclic C34 and C35 hopanes in lacustrine oils and source rocks. (October 2015) - Nytoft, Hans Peter; Ingermann Petersen, Henrik; Bryld Wessel Fyhn, Michael; Nielsen, Lars Henrik; Hovikoski, Jussi; Abatzis, Ioannis
Highlights: Novel C34 and C35 hexacyclic hopanes with a penta- or hexacyclic ring at C-22 identified. The hexacyclic ones are abundant in lacustrine oils but almost absent from marine oils. They are isomerized faster and have higher 22S/(22S + 22R) than pentacyclic hopanes. They are likely formed from penta- and hexafunctionalised BHPs. Abstract: Novel C34 and C35 hexacyclic hopanes having side chains with a pentacyclic or hexacyclic ring at C-22 are abundant in lacustrine oils and source rocks but almost absent from marine oils. The corresponding C34 and C35 hexacyclic hop-17(21)-enes were identified in thermally immature mudstones from Vietnam cored in the 500 m deep ENRECA-3 well. All the novel hexacyclic compounds were unambiguously identified by comparison with synthetic standards. Traces of heptacyclic hopanes were detected in a lacustrine oil from Thailand. The C34 and C35 hexacyclic hopanes have much longer gas chromatography (GC) retention times than the corresponding pentacyclic hopanes. They are isomerized faster at C-22 than the pentacyclic hopanes and their 22S/(22S + 22R) ratio values at equilibrium are much higher (0.8 for C34 ). Precursors could be penta- and hexafunctionalised hopanoids in cyanobacteria and methanotrophs.